2016
DOI: 10.7554/elife.15272
|View full text |Cite
|
Sign up to set email alerts
|

Mapping global environmental suitability for Zika virus

Abstract: Zika virus was discovered in Uganda in 1947 and is transmitted by Aedes mosquitoes, which also act as vectors for dengue and chikungunya viruses throughout much of the tropical world. In 2007, an outbreak in the Federated States of Micronesia sparked public health concern. In 2013, the virus began to spread across other parts of Oceania and in 2015, a large outbreak in Latin America began in Brazil. Possible associations with microcephaly and Guillain-Barré syndrome observed in this outbreak have raised concer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
382
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 329 publications
(391 citation statements)
references
References 105 publications
(132 reference statements)
6
382
1
2
Order By: Relevance
“…Ascertaining the portion of this population that is truly at risk is an important priority. One recent estimate 3 suggested that 5.42 million childbearing women live in areas of the Americas that are suitable for Zika occurrence. To improve on that estimate, which did not take into account the protective effects of herd immunity, we developed a new approach that combines classic results from epidemiological theory with seroprevalence data and highly spatially resolved data about drivers of transmission to make location-specific projections of epidemic attack rates.…”
mentioning
confidence: 99%
“…Ascertaining the portion of this population that is truly at risk is an important priority. One recent estimate 3 suggested that 5.42 million childbearing women live in areas of the Americas that are suitable for Zika occurrence. To improve on that estimate, which did not take into account the protective effects of herd immunity, we developed a new approach that combines classic results from epidemiological theory with seroprevalence data and highly spatially resolved data about drivers of transmission to make location-specific projections of epidemic attack rates.…”
mentioning
confidence: 99%
“…Use of GIS-based epidemiological maps allow to integrate preventive and control strategies, as well as public health policies, for joint control of this vector-borne disease in this and other areas of the country [4][5][6][7][8][9][16][17][18][19][20][21][22][23][24]. As other arboviruses are co-circulating (dengue, CHIKV and ZIKV), maps of them as well for co-infections will be also needed [16,17].…”
Section: -2016mentioning
confidence: 99%
“…In this setting use of GIS would be also at national and subnational levels to provide models about the influence and suitability of Zika given environmental and social factors [8,18]. Recent evidences indicated that 2015 El Niño caused extreme climatic conditions in Northeastern South America during winter and spring in the southern hemisphere, that might have contributed to the rapid dispersal of Zika virus in Brazil and other countries in the region, possibly including Colombia [19], as has been evidenced for dengue in different regions of this country [20,21].…”
Section: -2016mentioning
confidence: 99%
“…The model has been calibrated by using data from French Polynesia and the observed epidemic peak in Colombia (± 1 wk), as reported by Colombia's National Institute of Health (38); further research is needed to provide ZIKV-specific parameter estimates and more accurate local calibrations. Mosquito presence/absence maps are available from published data but have limitations as detailed in the literature (32,34,58). Sexual and other modes of transmission are not incorporated in the model.…”
Section: Projected Zikv Infections In Childbearing Women and Microcepmentioning
confidence: 99%
“…30). Furthermore, although mathematical and computational models have tackled the characterization of the transmissibility and potential burden of ZIKV (31)(32)(33)(34)(35), little is known about the global spread of the virus in 2014 and 2015, before the WHO's alert in early 2016.…”
mentioning
confidence: 99%